Словотвір жіночих варіантів імен у прибузьких говірках - Нестерчук, Оксана; Nesterchuk, Оksana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано творення жіночих варіантів імен прибужан, що постали внаслідок суфіксації від повної та усіченої основи офіційних імен, усічення та усічено-суфіксальних способів з їх різними комбінаціями. Крім цього, виявлено деривати лексичного творення. Зафіксовано одиничні варіанти, що належать конкретному носієві імені з найрізноманітнішими засобами вираження. The article analyzes the creation of women's names prybuzhan variants that arose as a result of suffixation of complete and truncated basis of official names, truncation and truncated suffix-ways with their various combinations. In addition, derivatives revealed lexical creation. A womanish repertoire mostly coincides with zagal'noukrainskim nominal creation. At the same time, single variants which belong to the concrete transmitter of the name with the most various facilities of expression are fixed. For creation of deminutivnikh variants 23 suffixes which give the name a zdribnilopestliviy tint in a value are used: -as′-a, -echk-a, -ik, -ichk-a, -k-a, -on′k-à, -ul′-a, -shk-a and others; 19 suffixes are with shrublet shade: -ar-a, -is′k-o, -ik-a, -op-a, -ut-a, -kh-a but other. Neutral in relation to the emotional colouring are variants of the names with suffixes -′à, -dz′-à, -in-a, -n′-à, -s′-à. Our material rotined that more frequent all the variants of the names of habitants of this territory are formed by a suffix and truncating with a suffix with different combinations. Not found out reduplikacii.
Word Formation in Female Version of the Name in the Dialects Bug
Keywords: жіночі варіанти імен; пестливі суфікси; збільшено-згрубілі суфікси; нейтральні суфікси; продуктивні типи; womanish variants of the names; tender; increased shrub; neutral suffixes; productive types